1988
DOI: 10.1007/bf01876161
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of stable alginate gel beads in electrolyte solutions using Ba2+ and Sr2+

Abstract: Alginate solutions with two different M/G (mannuronic acid/guluronic acid) ratios were added dropwise to SrCl 2 and BaCl 2 solutions. The low M/G ratios(0.27) St-and Ba-alginate gel beads were more chemically and physically stable in electrolyte solutions than conventional Caalginate gel beads. These gel beads with immobilized yeast cells had normal ethanol productivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Based on the results, the gelation period should be increased or the temperature changed to avoid the erosion of the calcium-alginate beads. Other alternative to increase the mechanical strength of the spheres could be use Sr 2 , because both, the chemical strength and the mechanical strength of Sr-alginate are known to be superior to those of Ca-alginate (Tanaka and Irie 1988;Sakurai et al 1999). Figure 5, shows the COD variation as a function of the time and distance (ports) in the reactor.…”
Section: Resultsmentioning
confidence: 98%
“…Based on the results, the gelation period should be increased or the temperature changed to avoid the erosion of the calcium-alginate beads. Other alternative to increase the mechanical strength of the spheres could be use Sr 2 , because both, the chemical strength and the mechanical strength of Sr-alginate are known to be superior to those of Ca-alginate (Tanaka and Irie 1988;Sakurai et al 1999). Figure 5, shows the COD variation as a function of the time and distance (ports) in the reactor.…”
Section: Resultsmentioning
confidence: 98%
“…Tanaka and Irie (1988) successfully substituted strontium and barium for calcium, but this type of biocatalyst bead would not be acceptable for citric acid production for the food industry. Consequently, the possibility of using glutaraldehyde to harden the alginate beads was investigated.…”
Section: Calcium-alginate-entrapped Yeast Biocatalyst Beads In Citricmentioning
confidence: 99%
“…Barium cross-linking enhances in vitro and in vivo long-term integrity compared to calcium [72,73], with barium alginate microcapsules used to protect allogeneic pancreatic islets for up to 350 days in a murine model [74]. Although to a lesser extent than the other high affinity options, Ba 2+ ions are toxic [75,76].…”
Section: Alginate Microencapsulationmentioning
confidence: 99%
“…With a weak polyelectrolyte attachment, the membrane detaches quickly and frequently after implantation. Various strategies for enhancing mechanical strength and long-term stability of alginate microcapsules have been studied in the past, including the use of different multivalent cations to form the core alginate hydrogel [72,74], different polycations on the alginate microcapsules [138], and tailor-made alginate to enhance the binding of PLL onto the alginate microcapsules [139]. More recently, Dusseault et al have demonstrated that covalently cross-linked alginate/PLL multilayer capsules [140] are sufficiently robust to prevent breakout of tumorigenic EL-4 thyoma cells, while the process itself is mild and does not adversely affect islet viability or function [141].…”
Section: Enhancing Structural Integrity Of Microcapsulesmentioning
confidence: 99%